Article Commentary: Recommendations for Integrating Peer Mentors in Hospital-Based Addiction Care. Issue 4 (October 2020) - Englander, Honora; Gregg, Jessica; Gullickson, Janie; Cochran-Dumas, Onesha; Colasurdo, Chris; Alla, Juliet; Collins, Devin; Nicolaidis, Christina
Legislators and health systems have recently begun to explore the use of peer mentors as part of hospital-based addiction teams. Integrating peers into hospitals is a complex undertaking still in its infancy. Peers' lived experience of addiction and its consequences, combined with their distance from medical culture and hierarchy, is at the core of their power – and creates inherent challenges in integrating peers into hospital settings. Successful integration of peers in hospitals has unique challenges for individual providers, health systems, and the peers themselves. We have included peers as part of a hospital-based addiction medicine team at our hospital since 2015. In this article, we outline some unique challenges, share lessons learned, and provide recommendations for integrating peers into hospital-based SUD care. Challenges include the rigid professional hierarchy of hospitals which contrasts with peers' role, which is built on shared life experience and relationship; different expectations regarding professional boundaries and sharing personal information; the intensity of the hospital environment; and, illness severity of hospitalized people which can be emotionally draining and increase peers' own risk for relapse. Recommendations focus on establishing a way to finance the peer program, clearly defining the peer role, creating a home base within hospital settings, creating a collaborative and structured process for hiring and retaining peers, identifying peers who are likely to succeed, providing initial and ongoing training to peers that extends beyond typical peer certification, ways to introduce peer program to hospital staff, and providing regular, meaningful supervision. We hope that our recommendations help other hospital systems capitalize on the practical lessons learned from our experience.